PFOA induces alteration in DNA methylation regulators and SARS-CoV-2 targets Ace2 and Tmprss2 in mouse lung tissues - Saeed Ahmad (Elsevier, 2021)
Perfluorooctanoic acid (PFOA), a ubiquitous environmental toxicant from the Per- and polyfluoroalkyl substances (PFAS) family has been implicated in toxicity of various organs. Several epidemiological studies have linked PFOA to different lung injuries and diseased conditions. However, the implication of PFOA in affecting epigenetic regulators and SARS-CoV-2 infection pathways in the lung are unknown. The present work explores the accumulation of PFOA in lungs and changes in mRNA expression of DNA methylation regulator genes DNA methyltransferases (Dnmts) and ten-eleven translocation (Tets) along with the membrane proteins angiotensin converting enzyme 2 (Ace2) and transmembrane Serine Protease 2 (Tmprss2) genes involved in the SARS-CoV-2 virus infection. CD1 mice were orally exposed to 5 and 20 mg/kg/day PFOA for 10 days and the lung tissues were analyzed using LCMS, qPCR, and pyrosequencing techniques. PFOA was shown to accumulate in the lung tissues and increase in a dose-dependent manner. Dnmts and Tets were significantly downregulated upon at least one of the PFOA dosing concentration, whereas Ace2 and Tmprss2 show significant increase in their expression level. Further, CpG islands in the promotor region of Tmprss2 exhibited significant hypomethylation in PFOA treated groups, which supports its increased gene expression level. Current study reveals the implication of PFOA induced DNA methylation changes in lungs and their possible role in upregulation of Ace2 and Tmprss2. It is possible that increased expression of these membrane receptors due to PFOA exposure can lead to higher susceptibility of SARS-CoV-2 infections.